The EMBARC European Bronchiectasis Registry: protocol for an international observational study. Issue 1 (20th January 2016) - Chalmers, James D.; Aliberti, Stefano; Polverino, Eva; Vendrell, Montserrat; Crichton, Megan; Loebinger, Michael; Dimakou, Katerina; Clifton, Ian; van der Eerden, Menno; Rohde, Gernot; Murris-Espin, Marlene; Masefield, Sarah; et al.
Bronchiectasis is one of the most neglected diseases in respiratory medicine. There are no approved therapies and few large-scale, representative epidemiological studies. The EMBARC (European Multicentre Bronchiectasis Audit and Research Collaboration) registry is a prospective, pan-European observational study of patients with bronchiectasis. The inclusion criterion is a primary clinical diagnosis of bronchiectasis consisting of: 1) a clinical history consistent with bronchiectasis; and 2) computed tomography demonstrating bronchiectasis. Core exclusion criteria are: 1) bronchiectasis due to known cystic fibrosis; 2) age <18 years; and 3) patients who are unable or unwilling to provide informed consent. The study aims to enrol 1000 patients by April 2016 across at least 20 European countries, and 10 000 patients by March 2020. Patients will undergo a comprehensive baseline assessment and will be followed up annually for up to 5 years with the goal of providing high-quality longitudinal data on outcomes, treatment patterns and quality of life. Data from the registry will be available in the form of annual reports. and will be disseminated in conference presentations and peer-reviewed publications. The European Bronchiectasis Registry aims to make a major contribution to understanding the natural history of the disease, as well as guiding evidence-based decision making and facilitating large randomised controlled trials. The European Bronchiectasis Registry will recruit 10 000 patients over 5 years http://ow.ly/Ul7Pd